1997
DOI: 10.1128/iai.65.4.1364-1369.1997
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 synthesis is a required step in trehalose dimycolate-induced activation of mouse peritoneal macrophages

Abstract: Trehalose dimycolate (TDM), a glycolipid present in the cell wall of Mycobacterium spp., is a powerful immunostimulant. TDM primes murine macrophages (M) to produce nitric oxide (NO) and to develop antitumoral activity upon activation with low doses of lipopolysaccharide (LPS). In this study, we investigated the ability of TDM to induce interleukin 12 (IL-12) and the role of this cytokine in TDM-induced activation of murine M. RNA isolated from peritoneal exudate cells (PEC) collected at different times after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Both LPS and lipoteichoic acid from gram-positive bacteria have been shown to induce IL-12 primarily through their interaction with CD14 [7]. Trehalose dimycolate, a glycolipid present in the cell wall of Mycobacterium tuberculosis [8], and glycoprotein fractions from Trypanosoma cruzi trypomastigotes [9] and Toxoplasma gondii tachyzoites [10] have been shown to induce IL-12. Other inducers of IL-12 include the recombinant Leishmania braziliensis antigen LeIF [11] and the CpG motifs contained in bacterial DNA [12].…”
Section: Production and Biological Functions Of Interleukin-12 (Il-12)mentioning
confidence: 99%
“…Both LPS and lipoteichoic acid from gram-positive bacteria have been shown to induce IL-12 primarily through their interaction with CD14 [7]. Trehalose dimycolate, a glycolipid present in the cell wall of Mycobacterium tuberculosis [8], and glycoprotein fractions from Trypanosoma cruzi trypomastigotes [9] and Toxoplasma gondii tachyzoites [10] have been shown to induce IL-12. Other inducers of IL-12 include the recombinant Leishmania braziliensis antigen LeIF [11] and the CpG motifs contained in bacterial DNA [12].…”
Section: Production and Biological Functions Of Interleukin-12 (Il-12)mentioning
confidence: 99%
“…TOM thus obviously stimulates important effector cells of innate immunity. Other works showed that TOM also supports an early adaptive immune response by inducing lL-12 and/or IFN-y (67,76). In particular the induction oflL-12 and the depletion of an NK T cell population implicated in the production of IL-4 (17), a cytokine promoting a Th2 response, prove that depending on the experimental conditions TOM can also produce a cytokine milieu supporting a Thl response (67,76).…”
Section: Cellular Immune Responsementioning
confidence: 96%
“…After 4 h, non-adherent cells were removed by washing with PBS and the properties of the macrophage monolayers were tested. Their ability to produce NO was measured by nitrite accumulation in the culture supernatants, and their antiproliferative activity was measured by their ability to inhibit the growth of P815 mastocytoma cells as described previously [14,15,20].…”
Section: In Vivo Priming Of Mouse Peritoneal Macrophages By Tdcmmentioning
confidence: 99%
“…We have previously shown that 7 days after i.p. injec-tion of particles of TDM isolated from mycobacteria, the macrophages harvested ex vivo from the peritoneal cavity of mice are primed [14,15,20,26]; primed macrophages can acquire an NO-dependent antiproliferative activity after a 4-h exposure to ng concentrations of LPS in vitro. Moreover, unlike resident or thioglycollate-elicited macrophages, they exhibit an oxidative burst after priming with a phorbol ester (PMA).…”
Section: In Vivo Priming Of Mouse Peritoneal Macrophages By Tdcmmentioning
confidence: 99%
See 1 more Smart Citation